Towards high‐resolution 4D flow MRI in the human aorta using kt‐GRAPPA and B1+ shimming at 7T. Issue 2 (3rd February 2016) - Schmitter, Sebastian; Schnell, Susanne; Uğurbil, Kâmil; Markl, Michael; Van de Moortele, Pierre‐François
Abstract : Purpose: To evaluate the feasibility of aortic 4D flow magnetic resonance imaging (MRI) at 7T with improved spatial resolution using kt‐GRAPPA acceleration while restricting acquisition time and to address radiofrequency (RF) excitation heterogeneities with B1+ shimming. Materials and Methods: 4D flow MRI data were obtained in the aorta of eight subjects using a 16‐channel transmit/receive coil array at 7T. Flow quantification and acquisition time were compared for a kt‐GRAPPA accelerated (R = 5) and a standard GRAPPA (R = 2) accelerated protocol. The impact of different dynamic B1+ shimming strategies on flow quantification was investigated. Two kt‐GRAPPA accelerated protocols with 1.2 × 1.2 × 1.2 mm 3 and 1.8 × 1.8 × 2.4 mm 3 spatial resolution were compared. Results: Using kt‐GRAPPA, we achieved a 4.3‐fold reduction in net acquisition time resulting in scan times of about 10 minutes. No significant effect on flow quantification was observed compared to standard GRAPPA with R = 2. Optimizing the B1+ fields for the aorta impacted significantly ( P < 0.05) the flow quantification while specific B1+ settings were required for respiration navigators. The high‐resolution protocol yielded similar flow quantification, but allowed the depiction of branching vessels. Conclusion: 7T in combination with B1+ shimming allows for high‐resolution 4D flow MRI acquisitions in the human aorta, while kt‐GRAPPA limits total scan times without affecting flow quantification. J. Magn. Reson. Imaging 2016;44:486–499.